Would the Objectives and Characteristics of Islamic Accounting for Islamic Business Organizations Meet the Islamic Socio-Economic Objectives? - Rizal Yaya (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2004)
Islam has a different worldview which affects the socio-economic activities of its adherents. As accounting is a social institution which should reflect the nuances of its society and help to achieve its socio-economic objectives, a different type of accounting is required as compared to the conventional accounting of capitalistic society. Research on Islamic accounting is still at an exploratory stage; its pioneers trying to develop a theoretical framework for Islamic accounting using various methodologies. In common with the development of conventional accounting, the search is on for the objectives and characteristics of Islamic accounting as a foundation on which to lay its principles, conventions, rules and standards. This article explores the emerging issues in this development and searches for patterns in the debate on Islamic accounting theory and evaluate these different methodologies and approaches suggested in the literature used to develop Islamic accounting theory. The writer finds that a number of the proposed objectives and characteristics of Islamic accounting are doubted in meeting the objectives of Islamic teachings.Keywords: Islamic accounting theory, socio-economic objective, Value Added Statement.